Reactive-loaded antenna designs for ultra-wideband (UWB) applications - Siti Zubaidah Aziz (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
Objectives of the study are listed below ; to design and miniaturize ultra-wideband (UWB) antenna at frequency of 3.1 GHz to 10.6 GHz by using reactive-loaded technique ; to produce stable and omni-directional pattern within the specified operating bandwidth by partially truncating the ground plane of antenna ; to produce high gain UWB antenna by combiningthe reactive-loaded technique with conductor-backed plane.